PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP KUALITAS LABA PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - Ayu Puspitaningtyas (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2020)
This study aims to find out how the simultaneous influence receivabley turnover and inventory turnover on the earning quality of automotive and componens companies This research uses purposive sampling in taking data. The data collected will be analyzed using multiple linear analysis. The result of this research is (1) there is negative significant influence from receivable turnover variable to earning quality, (2) there is positif significant influence from inventory turnover variable to earning quality, (3) there is a significant effect of receivable turnover and inventory turnover value addedon earning quality simultaneously.